Obesity adversely affects serum anti-müllerian hormone (AMH) levels in Caucasian women - Moy, Vicky (J Assist Reprod Genet, 2015)
OBJECTIVE: Previous studies regarding the effect of obesity on serum anti-müllerian hormone (AMH) levels have been conflicting. Our aim was to determine the effect of obesity on serum AMH levels among women from different racial backgrounds. METHODS: The medical records of 350 women (159 Caucasian, 99 African-American, 58 Hispanic, 34 Asian with ages 16–46) evaluated for infertility at an academic-affiliated center and who had AMH levels measured as part of their evaluation were reviewed. Age, AMH, body mass index (BMI), self-reported race, etiology of infertility, smoking history, maximum serum early follicular follicle-stimulating hormone (FSH) levels, antral follicle count (AFC), and history of ovarian surgery, chemotherapy, or radiotherapy were recorded. RESULTS: Age correlated negatively with AMH and antral follicle count across all races (p < 0.05). After adjusting for age, polycystic ovary syndrome diagnosis, and smoking, elevated BMI had a negative correlation with AMH in Caucasian women (β = 0.17, p = 0.01) but not in African-American, Hispanic, or Asian women. CONCLUSION: Elevated BMI correlates negatively with AMH in Caucasian women but not in African-American, Hispanic, or Asian women. Additional studies are needed to elucidate further the effect of race on the interaction between obesity and ovarian reserve.